Analysis of Self-Estimated Pricing (HPS) in the Procurement Department Units 1&2 PT. PJB UP Paiton: Analisis Penentuan Harga Perkiraan Sendiri (HPS) di Bagian Pengadaan Unit 1&2 PT. PJB UP Paiton - Rizki, Abdur; Dwi Iryaning Handayani; Yustina Suhandini (Universitas Muhammadiyah Sidoarjo, 2023)
Self-Estimated Price (HPS) is an assumed cost for the procurement of goods and services in accordance with predetermined provisions and sourced from accountable data. In the field of procurement PT. PJB UP Paiton Unit 1&2 still has several errors in determining the HPS which can result in a failed auction. This study uses simple statistical techniques and also uses the Statistical Product and Service Solutions (SPSS) application so that the price intervals used are maximum HPS and minimum HPS. The price interval is the lowest and highest price limits used as the basis for determining the price of goods and services. In determining the HPS in the procurement of goods and services PT. PJB UP Paiton, calculates the HPS using an operational budget that uses five data sources in its determination. Data sources used in determining the HPS are market price data, previous contact prices, target price proposal prices and comparative study prices. The results of the HPS calculation for the procurement of 500 work vests, so that a minimum HPS of Rp. 52,250,000 and a maximum HPS of Rp. 56,080,200. In addition, the authors calculated the procurement of panel wall installation services with a size of 2.5 x 10 meters, so that a minimum HPS of Rp. 9,761,345 and a maximum HPS of Rp. 9,996,250.